INTEGRASI NILAI TRADISI PERANG KETUPAT DALAM PENDIDIKAN KARAKTER PESERTA DIDIK DI SMA N 1 TEMPILANG, BANGKA BELITUNG - Mizlan; Zalila, Nur (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study aims to examine the integration of traditional Ketupat War values in character education for students at SMA Negeri 1 Tempilang, Bangka Belitung. Using a qualitative case study approach, data was collected through interviews, observations, and documentation involving the school principal, teachers, and 11th-grade students. The research findings indicate that values such as cooperation, tolerance, brotherhood, responsibility, and cultural appreciation have been successfully internalized through various activities based on local traditions. The Ketupat War tradition is not only a medium for cultural preservation but also an effective and contextual moral education tool. The role of teachers as facilitators is crucial in incorporating character values into learning, while students demonstrate positive responses and significant changes in social attitudes. Challenges in integrating traditional values, such as the diversity of students' backgrounds, can be addressed through contextual approaches and the use of digital media. This study recommends the implementation of similar approaches in other regions to expand the model of education based on local wisdom that is adaptive to the times.